Constructing self-standing and non-precious metal heterogeneous nanowire arrays as high-performance oxygen evolution electrocatalysts: Beyond the electronegativity effect of the substrate - Chen, G.; Guo, Y.; Miao, S.; Sun, H.; Gu, B.; Li, W.; Zhong, Y.; Zhou, W.; Shao, Zongping (Elsevier SA, 2018)
© 2018 Elsevier B.V. Self-standing nanowires are the focus of intense interest as oxygen evolution reaction catalysts due to their natural advantages. However, the role of the substrate used for self-standing nanowires in oxygen evolution reaction is not fully investigated. Herein, we report that the oxygen evolution reaction activity is closely associated with the substrate. The oxygen evolution reaction activity of cobalt oxide catalysts is enhanced with the increasing electronegativity of the substrates, while iron oxide catalysts break this rule due to the stronger synergistic interplay between iron and copper compared to that between iron and gold. Under the guidance of these findings, we construct a highly active and robust non-precious-metal CuO@CoFeOxself-standing nanowire electrocatalyst, which shows a constant current density of 10 mA cm-2at an overpotential of 0.36 V for 300 h continuously without noticeable degradation in 0.1 M KOH solution. Moreover, the CuO@CoFeOxnanowire anode coupled with a Pt-Ni foam cathode shows an attractive overpotential of 0.39 V to provide a current density of 10 mA cm-2for water electrolysis in 1.0 M KOH solution.